Regulatory observations in bioanalytical determinations. (July 2010) - Viswanathan, CT
The concept of measuring analytes in biological media is a long-established area of the quantitative sciences that is employed in many sectors. While academic research and R&D units of private firms have been in the forefront of developing complex methodologies, it is the regulatory environment that has brought the focus and rigor to the quality control of the quantitative determination of drug concentration in biological samples. In this article, the author examines the regulatory findings discovered during the course of several years of auditing bioanalytical work. The outcomes of these findings underscore the importance of quality method validation to ensure the reliability of the data generated. The failure to ensure the reliability of these data can lead to potential risks in the health management of millions of people in the USA.